1990
DOI: 10.11150/kansenshogakuzasshi1970.64.257
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Enteropathogens by Clostridium butyricum MIYAIRI 588

Abstract: The inhibitory effect of Clostridium butyricum MIYAIRI 588 against various enteropathogens was investigated in mixed cultures. It was observed that C. butyricum M588 inhibited the growth of Vibrio cholerae O1, V. cholerae non-O1, Aeromonas hydrophila, and Shigella flexneri. Considering that the interaction between C. butyricum and Shigella is especially important because of their proliferation site in the lower intestine, further examinations were carried out on Shigella in particular. Results were as follows:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Clostridium butyricum found in soil and intestines of healthy animals and humans is a butyric-acid produce and gram-positive bacterium (Finegold et al 1983), and some strains have been used as probiotics in both animals and humans (Han et al 1984;Kuroiwa et al 1990). In our previous work, it was demonstrated that the strain Cl.…”
Section: Introductionmentioning
confidence: 99%
“…Clostridium butyricum found in soil and intestines of healthy animals and humans is a butyric-acid produce and gram-positive bacterium (Finegold et al 1983), and some strains have been used as probiotics in both animals and humans (Han et al 1984;Kuroiwa et al 1990). In our previous work, it was demonstrated that the strain Cl.…”
Section: Introductionmentioning
confidence: 99%
“…Some C. butyricum strains are used as probiotics as beneficial bacteria (7,14,22), whereas a few strains have been reported to be pathogenic (1,11). It would therefore be interesting to determine the degree of genotypic and/or phenotypic divergence among the C. butyricum strains.…”
Section: Discussionmentioning
confidence: 99%
“…(8) The present study used MIYAIRI 588, which is a common strain of Clostridium butyricum, which stimulates polyclonal mucosal immune activity and inhibits multiplication of Vibrio cholerae, Aeromonas hydrophila, and Shigella flexneri. (9,10) It also has preventive and therapeutic effects on enterohemorrhagic Escherichia coli (O157) infections, (11) decreases the toxicity of Clostridium difficile, (12) and suppresses progression of nonalcoholic steatohepatitis. (13,14) MIYAIRI 588 is effective in treating antibiotic-associated diarrhea in children because it normalizes intestinal flora.…”
mentioning
confidence: 99%